The Social Function of Food‐Associated Calls in Male Chimpanzees. Issue 7 (10th January 2013) - FEDUREK, PAWEL; SLOCOMBE, KATIE E.; Higham, James P.; Semple, Stuart
<x xml:space="preserve">Abstract</x> There is an ongoing debate about the adaptive function of chimpanzee's food‐associated calls. Here, we tested a new hypothesis that food‐associated calls in male chimpanzees function to signal that the calling individual is likely to initiate or prolong feeding. We propose that the signal functions to coordinate activities between individuals and that its ultimate function is to retain the nearby individuals in proximity. To test this hypothesis, we collected data on social and ecological correlates of food‐associates calls in male chimpanzees. The results of this study, which was conducted on the Kanyawara community in the Kibale National Park, Uganda, show that males tended to feed for significantly longer after giving food‐associated calls upon initiating feeding than after remaining silent. The type of audience had a significant effect on food calling, with males producing food‐associated calls more often when males rather than females and preferred rather than neutral male social partners were in close proximity. However, the total party or male party size did not correlate with food calling behaviors, suggesting that the signal "targets" those in close proximity. Finally, a male feeding partner was more likely to remain with the focal until the end of a feeding bout after the focal gave a food‐associated call at the beginning of the feeding bout than when he was silent. These results support our hypothesis and suggest that one of the functions of food calling in chimpanzees might be signaling that the caller is likely to initiate and prolong a feeding bout. This information might be used by receivers to make the decision whether or not to stay with the calling individual on a feeding patch or leave him (fission). The study suggests therefore that ultimately the function of food calling might be to coordinate feeding behaviors between males. Am. J. Primatol. 75:726‐739, 2013. © 2013 Wiley Periodicals, Inc.